Reimagining the "Third Voice": A Study of Optimal Performance Styles for Viola Solos in Shostakovich's Prelude (from the Concerto in G Major, arr. by Akutagawa) - Nasution, Nabila; Wijaksana, Bambang; Hendri, Yon; Awerman, Awerman (Scoring: Journal of Film Music, 2025)
This study investigates the spectrum of performance styles considered“optimal” for the viola solo in the Prelude from Dmitri Shostakovich’sConcerto in G Major (as arranged for viola and piano by YasushiAkutagawa). While often overshadowed by the orchestral context of theoriginal concerto for cello, this transcription presents a uniquemicrocosm of Shostakovich’s musical language, characterized by incisivesatire, lyrical despair, and structural ambiguities that require profoundinterpretive decisions by the viola player. Moving beyond prescriptivenotions of a single “best” style, this study employs a hybrid methodologyof performance analysis and practice-based inquiry. Through aComparative analysis of ten commercially available recordings byrenowned viola players (e.g., Bashmet, Imai, Várady), we identify threedominant interpretive paradigms: the “Symphonic-Narrative,”“Chamber-Intimate,” and “Modernist-Deconstructive” approaches.Subsequently, a practice-based component, involving deliberate stylisticExperimentation by the principal researcher-performer examines thetechnical and expressive implications of each paradigm. The findingssuggest that “optimal” style depends on successfully aligning theperformer’s technical execution (e.g., bow distribution, vibrato width,intonation precision in ambiguous harmonies) with a coherent, context-based hermeneutic. This study argues that pedagogical discourse on thiswork should shift from seeking definitive interpretations towarddeveloping the performer’s “hermeneutical flexibility”—the ability toconsciously navigate and justify stylistic choices within Shostakovich’scomplex aesthetic framework. This research contributes to violaperformance pedagogy and music cognitive science by modeling ananalytical and reflective framework for interpreting the 20th-centuryrepertoire.